COMPARISON OF THE ANTIOXIDANT CAPACITY OF AN IMPORTANT HEPATOPROTECTIVE PLANTS (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Currently there has been an increased interest globally to identify antioxidant compounds that are pharmacologically potent and have low or no side effects for use in preventive medicine and the food industry. As plants produce significant amount of antioxidants to prevent the oxidative stress caused by photons and oxygen, they represent a potential source of new compounds with antioxidant activity. Commonly used medicinal plant extracts with standardized content of polyphenols were investigated for their antioxidant activity (AA). In the present paper ten plants (Picrorrhiza kurroa, Tephrosia purpurea, Terminalia arjuna, Tinospora cordifolia, Glycyrrhiza glabra, Azadirachta indica, Apium graveolens, Swertia chirata, Phyllanthus amarus, and Aloe vera) and their possible constituents responsible for its antioxidant property were compared by reducing power, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity method. The plants described contain antioxidant principles that can explain and justify their use in traditional medicine (Hepatoprotective) in the past as well as the present. These results suggest that AA determination is of interest for a comparative evaluation of in vitro antioxidant potential, but it needs to be combined with in vivo data for adequate assessment of the antioxidant capacity of medicinal plant extracts.